The Elegantness of the Muhammadiyah Leadership Election System and Traditions: Case Study in Southeast Sulawesi - Alifuddin, Muhammad; Yusuf, Yusuf; Ahmadi, Ahmadi; Anhusadar, Laode (Al-Izzah: Jurnal Hasil-Hasil Penelitian, 2024)
This study aims to explain the uniqueness of the tradition of electing Muhammadiyah administrators in Southeast Sulawesi. Research data were obtained through participatory observations, in-depth interviews, and document reviews. Data analysis was performed using the Miles and Huberman paradigm combined with the Von Eckarberg hermeneutic phenomenological analysis model. The results of this study indicate that the succession of the Muhammadiyah Southeast Sulawesi Regional Leadership was held through an election mechanism with a voting system to elect 13 formators. Although the process was full of dialectical thoughts flowing from the participants of the deliberation, the process involving 142 voters, representatives of 16 Muhammadiyah Regional Leaders, took place elegantly, democratically, and without noise. The elegance of deliberation in the Muhammadiyah environment occurred not only because of the rationality of the Muhammadiyah people but also because the egalitarian collegial system in Muhammadiyah was very prominent. This made it easy for them to make decisions by consensus when appointing the Chairperson and Secretary. The description of a number of sosial analysts regarding the Muhammadiyah Congresses in Yogyakarta, Makassar and Solo which took place without "intrigue" and political interest, was also reflected in the Muhammadiyah Southeast Sulawesi Regional Conference as an event to elect the Muhammadiyah Regional Leadership for the 2022-2027 period. The success of Muhammadiyah Southeast Sulawesi in creating a peaceful situation in the leadership succession event was supported by three factors: egalitarianism and mainstreaming of consensus, organizational commitment, and consistency in implementing organizational rules